PENGARUH VARIASI KONSENTRASI SARI PATI BUAH SUKUN SEBAGAI ALTERNATIF MEDIA SEMI SINTETIK PADA PERTUMBUHAN JAMUR Candida albicans - Reza Yuliana; M. Taufiq Qurrohman (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2022)
Gold standard examination Candida sp. is a culture test. The abundance natural resources in Indonesia encourages researchers to take advantage the wealth of natural resources to create alternative semi-synthetic media for mushroom growth from breadfruit. The purpose of this study was determining the effective concentration of alternative semi-synthetic media of breadfruit essence as growth medium for the fungus Candida albicans. This research is experimental study. Observations were made macroscopically and confirmed microscopically. The results showed that average growth of the colonies on PDA media was 15.50, for the alternative breadfruit media the average of colonies was 24.50 (100% concentration), 19.75 (90% concentration), 19.50 (80% concentration), 16.00 (70% concentration), 15.50 (60% concentration). The results of the ANOVA test obtained value <0.05, so H1 was accepted there was a significant difference in the average growth of fungi in the media of breadfruit essence. The conclusion from this research is that the concentration of 60% breadfruit essence is the effective for growing Candida albicans.